1994
DOI: 10.1073/pnas.91.24.11358
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule dynamics in vitro are regulated by the tubulin isotype composition.

Abstract: The growing and shortening dynamics of individual bovine brain microtubules at their plus ends at steady state in vitro, assembled from isotypically pure a4u, abim, or acsv tubulin dimers, were determined by differential interference contrast video microscopy. Microtubules assembled from the purified afm isotype were considerably more dynamic than microtubules made from the apu or a4iv isotypes or from unfractionated phosphocellulose-purified tubulin. Furthermore, increasing the proportion of the aoil isotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
322
1
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(342 citation statements)
references
References 31 publications
18
322
1
1
Order By: Relevance
“…In this study, we observed an increase in P. (Jordan et al, 1992;Derry et al, 1995;Dhamodharan et al, 1995). Using purified 0-tubulin isotypes, Panda et al (1994) have shown that microtubule dynamics are regulated by the tubulin isotype composition.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, we observed an increase in P. (Jordan et al, 1992;Derry et al, 1995;Dhamodharan et al, 1995). Using purified 0-tubulin isotypes, Panda et al (1994) have shown that microtubule dynamics are regulated by the tubulin isotype composition.…”
Section: Discussionsupporting
confidence: 58%
“…We also observed that the relative proportion of Class IV was greatly increased (seven-fold), whereas the proportions of classes I and II were reduced in mut-p53 cells. The b-tubulin isotype composition of microtubules in vitro can alter their dynamic properties (Panda et al, 1994;Derry et al, 1997), suggesting that the differences we observed in isotype composition between wt-p53 and mut-p53 cells may contribute to the observed differences in dynamics. These alterations may also be involved in drug resistance to microtubule-targeted drugs (Burkhart et al, 2001).…”
Section: Discussionmentioning
confidence: 81%
“…Several in vitro studies have demonstrated that the β tubulin isotype composition of microtubules determines the differences in their functions including dynamics, assembly properties and sensitivity to antimicrotubule agents (Banerjee et al, 1990Benerjee and Luduena, 1992;Luduena, 1993, 1994;Panda et al, 1994Panda et al, , 1997Derry et al, 1997). Because antimicrotubule agents are widely used in cancer therapy, tubulin isotype composition of tumour cells may be an important factor in the success of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…αβ III dimers assembled at a very slow rate and had the highest critical concentration. However, in vitro analysis by Panda et al (1994) has shown that microtubules assembled from αβ III dimers were more dynamic than the microtubules from αβ II and αβ IV isotypes. They further demonstrated that addition of αβ II dimers to αβ III dimers suppressed microtubule dynamics.…”
Section: Discussionmentioning
confidence: 99%